Scan-classify-overlay model for Bozo and Bangime nominal tones - Jeffrey Heath (Mandenkan)
Nominal compounds (N-N) and noun-adjective (N-Adj) sequences share a distinctive morphotonology and behave as (extended) prosodic words in four Bozo languages studied. Input N and Adj stems of various tone melodies are scanned for tonal characteristics that classify the numerous melodies into just two melodic superclasses for initials. Separately, finals are also scanned and classified. The criterial tonal feature varies from language to language and from initial to final; it may be the leftmost tone element or a configuration (level versus contour). Tone overlays are then associated with the initial, the final, or both jointly. In some cases, the lexical melody of the initial is overwritten locally, but is expressed at a distance by determining or at least influencing the overlay on the final.In the neighboring isolate Bangime, a structurally similar scan-classify-overlay system is at work in definite and possessed NPs.In Bozo and Bangime, an overlaid tone pattern may differ from or even invert the (lexical) melody. However, because overlays are associated with melodic superclasses, they allow partial recovery of melodies by listeners. The scan-classify-overlay model is distinct both from ordinary tonal morphophonology (which directly operates on lexical tones) and from true replacive tonal ablaut (which irrecoverably erases melodies).